Modifikasi Alat Pemintal Benang Sutera Untuk Industri Rumah Tangga - Abdul Salam; Muh Iswar; Bensar Pali; Agustinus Anggai; Janchristo Rantemangnga (Politeknik Negeri Ujung Pandang, 2019)
This study aims to determine the yarn spinning time, spinning equipment manufacturing costs, and haspel shaft spinning. Basic design is done by data collection, direct visits to the silk farmers' groups, tool design, tool manufacturing, performance testing tools, analysis, calculating costs and tool manufacturing. In accordance with the testing of the spinning machine, the total working time is 8 hours / day for 3.36 kg of silk yarn, the spinning equipment manufacturing cost is Rp. 5,102,534.71. Whereas BEP is achieved when the sale of spinning machines is at least 1 unit / month or when income is Rp. 5,621,064.